Influence of 2,4-D and BAP on callus growth and the subsequent regeneration of somatic embryos in long-term cultures of Pelargonium x domesticum cv. Madame Layal - Haensch, Klaus-Thomas (Electronic Journal of Biotechnology, 2007)
This long-term study demonstrates for the first time that it is possible to propagate embryogenic cultures in pelargoniums and to subsequently initiate the differentiation of embryos using the cultivar Madame Layal (Pelargonium x domesticum). Propagation of callus was only possible with combinations of 2,4-dichlorophenoxyacetic acid (2,4-D) and 6-benzylaminopurine (BAP), which gave rise to embryos from the primary culture stage on. However, the propagation of cells, as well as the differentiation of embryos, was inhibited by a continuous application of these growth regulators. For this reason, a long period on medium lacking growth regulators was necessary before the differentiation of embryos occurred again. The consequences for improving the propagation of embryogenic cultures in pelargoniums are discussed.